Use of a universal targeting CAR T cell to simultaneously kill cancer cells and cancer-associated fibroblasts - Huang, Bo; Zheng, Suilan; Sudarshan, Kasireddy; Mukkamala, Ramesh; Srinivasarao, Madduri; Sardesai, Tushar; Yang, Xiaofei; Chu, Haiyan; Low, Philip S. (Frontiers in Immunology, 2025)
CAR T cells therapies have demonstrated success in treating hematologic malignancies, but have proven less effective in eradicating solid tumors. While suppressive immune cells may contribute to reduced CAR T cell efficacies in malignant masses, cancer-associated fibroblasts (CAFs) are also believed to facilitate tumor survival by secreting growth factors, immunosuppressive cytokines, and extracellular matrix components that inhibit drug and immune cell filtration and facilitate metastasis. In an effort to eliminate both CAFs and cancer cells simultaneously, we have employed a universal CAR T cell that can attack both cell types when supplemented with appropriate bispecific adapters. We show here that tumor regression is indeed enhanced when CAR T cells are directed to concurrently kill both cancer cells and CAFs. We further demonstrate that simultaneous targeting of both cell types enhances CAR T cell proliferation, activation, tumor infiltration, and tumor distribution relative to targeting only a single cell type. Because all of these benefits are achieved in both cold and hot tumors without significant toxicity, we conclude that use of a universal CAR T cell in combination with multiple bispecific adapters can provide a safe, potent, cost-effective, and scalable alternative to the treatment of solid tumors with conventional CAR T cells.